Chemical Composition, Antioxidant, and Antimicrobial Activities of the Leaf and Fruit Essential Oils of the West African Plum, Vitex doniana - Jahnissi Frimpomah Odoom; Caleb Impraim Aboagye; Philipina Acheampong; Isaac Asiamah; Godfred Darko; Lawrence Sheringham Borquaye (Journal of Chemistry)
Vitex doniana (West African plum or black plum) is a plant with varying phytoconstituents and biological activities across different countries. In this study, essential oils extracted from the leaves and fruits of Vitex doniana cultivated in Ghana were investigated for their antimicrobial and antioxidant activities. The antioxidant actions of the essential oils were determined using hydrogen peroxide (H2O2), phosphomolybdenum, thiobarbituric acid reactive substances (TBARS), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays. For both essential oils, the total antioxidant capacities ranged from 44 to 68 µg/g AAE, the IC50 values for H2O2 scavenging activity were between 87 and 242 µg/mL, whereas that for DPPH assay were between 322 and 599 µg/mL. The IC50 for the TBARS assay for both essential oils also ranged from 247 to 414 µg/mL. The antimicrobial activities of the essential oils were investigated using the broth dilution assay. The minimum inhibition concentration for the essential oils ranged from 12.5 to 50 mg/mL. Biofilm inhibitory activity was also evaluated for both essential oils, and the fruit essential oil showed a half-maximal inhibition of biofilm formation (BIC50) at 44.40 ± 0.6 mg/mL, whereas the BIC50 value of the leaf essential oil was 109.1 ± 0.9 mg/mL. The fruit essential oil was superior to the leaf essential oil in inhibiting the secretion of pyoverdine. Molecular docking analyses suggested that methyl cinnamate, ethyl cinnamate, p-menth-4-en-3-one, trans-α-ionone, benzyl benzoate, isobutyl cinnamate, and folic acid likely interacted with LasR and algC proteins, and hence, contributed to the inhibition of biofilm formation and pyoverdine secretion. Essential oils from Vitex doniana could, therefore, be exploited as a natural source of radical scavenging and antimicrobial agents and could be useful in the pharmaceutical, food, and cosmetic industries.